2009
DOI: 10.1021/jp901055v
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Rhodium Nanostructures through the Evolution of Microgalvanic Cells and Their Enhanced Electrocatalytic Activity for Formaldehyde Oxidation

Abstract: Shape-controlled morphological evolution of nanostructured Rh has been demonstrated with the help of a galvanic displacement reaction using Al in 1 mM aqueous Rh(III) chloride at an open circuit potential 0.99 V and at a temperature of 273 K (room temperature). Nanospheres composed of small nanoparticles of size around 2.9 ± 0.4 nm having uniform distribution with a FCC pattern have been evolved during the course of the reaction. Electrochemical results coupled with structural and morphological characterizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…The electrooxidation of formaldehyde on metal, such as Pt, Cu, Rh et al, has been widely reported [1]- [5]. In aqueous solutiongs, formaldehyde exists mainly in its hydrated form, methylene glycol (H 2 C(OH) 2 ), and the following electrochemical oxidation maybe occur on Ag surface: …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrooxidation of formaldehyde on metal, such as Pt, Cu, Rh et al, has been widely reported [1]- [5]. In aqueous solutiongs, formaldehyde exists mainly in its hydrated form, methylene glycol (H 2 C(OH) 2 ), and the following electrochemical oxidation maybe occur on Ag surface: …”
Section: Resultsmentioning
confidence: 99%
“…Formaldehyde is also one of the initial products of methanol oxidation which has its fundamental and technological importance in industrial catalytic processes [2]. The electrooxidation mechanism of formaldehyde has been widely investigated on Pt [3], Pd [4], and Rh [5] electrodes which are mostly in connection with fuel cells and sensors. Whereas, these anodic materials are the noble metal with their scarcity, and can't lower the commercial cost.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, significant progresses have been made for the size- and shape-control of NMNPs by tuning the crystal growth kinetics in numerous wet-chemistry approaches. Among various NMNPs, rhodium (Rh) is particularly known for its critical role in diverse catalytic reactions, such as CO oxidation [22, 23, 24, 25], NO reduction [26, 27, 28], hydrogenation [29, 30, 31, 32, 33], hydroformylation [34, 35, 36], and electro-oxidation [37, 38, 39, 40]. Moreover, Rh-based catalysts are especially stable for use under harsh reaction conditions because of its strong resistance to the etching of acid/base and heat.…”
Section: Introductionmentioning
confidence: 99%
“…Sathe et al. prepared rhodium nanostructures through the evolution of microgalvanic cells 11. These rhodium nanostructures exhibit enhanced electrocatalytic activity toward many fuel cell reactions as demonstrated by formaldehyde oxidation in 0.5 M NaOH.…”
Section: Introductionmentioning
confidence: 99%